Prediction and analysis of rotor tip-clearance flows using large-eddy simulation - You, D.; Wang, M.; Moin, P.; Mittal, R. (Proceedings : Users Group Conference : Williamsburg, Virginia, June 7-11, 2004, 2004)
In order to analyze the dynamics of rotor tip-clearance flow and determine the underlying mechanism for the tip-leakage cavitation, a newly developed large-eddy simulation (LES) solver which combines an immersed-boundary method with a generalized curvilinear structured grid has been employed. An analysis of the LES results has been performed to understand the mean flow field, turbulence characteristics, vortex dynamics, and pressure fluctuations in the turbomachinery cascade with tip gap. Based on thorough analysis of the flow field, a guideline for reducing viscous losses in the cascade is provided. Analyses of the energy spectra and space-time correlations of the velocity fluctuations suggest that the tip-leakage vortex is subject to pitchwise wandering motion. The largest pressure drop and most intense pressure fluctuations due to the formation of the tip-leakage vortex are found in the region where the tip-leakage vortex is strongest. The effects of tip-gap size and an end-wall groove on the tip-clearance vortical structures and on the velocity and pressure fields have been investigated to explore ways for minimizing the detrimental effects of cavitation. Attempts to investigate the vortex-rotor interaction and to enhance the LES capability for realistic rotors are also discussed.